Pengaruh Promosi, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Batik Madura Pada Galery Pesona Bangkalan - Khusnul Khotimah; Pribanus Wantara (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The study aims to test and analyze the impact of promotions, prices and the quality of products on the batik madura purchase decision on the charm fisheries. The study is using a predictive quantitative approach, the population in this study is the customer who used to buy batik madura at the charm gallery of the banker. With as many as 60 respondents taken using sampling techniques. Data collected using a questionnaire. The tools of analysis in the study employ instrument testing, classic assumptions test, data analysis (linear regression analysis berganda, test t, test f and r2's coefficient determinations). The results of the data prepared in SPSS 23 result in that promotion is partial to positive and significant to purchase decisions, prices are partial to positive and significant to purchase decisions and product quality. Based on the simultaneous promotion of f, prices and quality products have a positive and significant impact on purchasing decisions.